Development and Evaluation of Hydrogel Containing Ocimum Sanctum and Boswellia Serrata Extracts for Anti-Inflammatory Propriety - Agrawal, Km Muskan; Mittal, Anuj (Journal of Neonatal Surgery, 2025)
Development and assessment of a hydrogel formulation incorporating ocimum sanctum, Indian Frankincense (Boswellia Serrata) extracts for anti-inflammatory activity. A ethanolic fraction was produced by partitioning the ethanol, of O. sanctum leaf powder extract and Frankincense resin (Gum). In separate containers, 50 ml each of chloroform, n-hexane, ethyl acetate, and double distilled water were combined. For the hydrogel synthesis, different proportions of aloe and ocimum sanctum and Indian Frankincense (Boswellia Serrata) were mixed with different proportions of propylene, methyl paraben and Carbopol 940. The ideal physical characteristics, pH level, homogeneity, viscosity, release profile, medication content, and irritation potential of the produced hydrogel were determined through characterization. The protein/albumin denaturation bioassay will used to evaluate the anti-inflammatory impact of the optimized hydrogel. Because the rules established by the CPCSEA, which control the use of animals in drug research, necessitated this review. When there are viable alternatives to using animals, these rules demand a good reason for their use. Ethical concerns take precedence. Most proteins lose their biological activity when denaturation occurs. It is well-established that albumin denaturation causes inflammation.